FACTORS AFFECTING THE LEVEL OF WORKING CAPITAL FINANCING: THIRD-PARTY FUNDS, FINANCING TO DEPOSIT RATIO (FDR), AND NON-PERFORMING FINANCING (NPF) AT ISLAMIC COMMERCIAL BANKS IN INDONESIA PERIOD 2019-2024 - Mahdalena Mahdalena; Rahmawati Khoiriyah (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study examines the effects of Third-Party Funds (DPK), Financing-to-Deposit Ratio (FDR), and Non-Performing Financing (NPF) on working capital financing in Islamic Commercial Banks in Indonesia during 2019–2024. The research employs a quantitative approach using panel data derived from the annual financial reports of Islamic commercial banks. Panel data regression analysis was conducted using a random-effects model (REM), as indicated by the Chow, Hausman, and Lagrange Multiplier tests. The results suggest that Third-Party Funds have a positive and significant effect on working capital financing, whereas FDR and NPF do not have a statistically significant effect. Simultaneously, all independent variables significantly affect working capital financing, with an adjusted R-squared value of 77.1%. These findings suggest that Islamic banks' capacity to expand working capital financing is primarily driven by their effectiveness in mobilizing Third-Party Funds, rather than by liquidity ratios or financing risk indicators alone. Therefore, Islamic banks are encouraged to strengthen digital-based fundraising strategies, enhance depositor retention, and develop stable funding structures to support sustainable growth in working capital financing.